Modified ZERILLI-ARMSTRONG model for 21-4N heat-resistant steel - X. M. Huang; H. Y. Long; Y. M. Li; H. L. Duan (Metalurgija, 2020)
The Gleeble - 1500D thermal simulator was used to conduct the isothermal compression test of 21 - 4N heat-resistant steel under the T range of 1 273 - 1 453 K and ε̇ of 0,01 – 10 s-1. Using the obtained stress - strain data, various parameters of the modified Zerilli-Armstrong (m – Z - A) model were calculated. The constitutive equations of 21 - 4N heat-resistant steel based on the m – Z - A were established. The m – Z - A model can well describe the rheological behavior of 21 - 4N heat-resistant steel. The simulation process can be completed successfully, indicating that the established models can be used for the simulation study of thermal deformation of 21 - 4N heat-resistant steel and are correct. The results can provide some important basic data for the simulation of 21 - 4N heat resistant steel on plastic deformation process.